Study on Heart Failure Patients Admitted in National Institute of Cardiovascular Diseases - Alam, Nur; Majumder, Abdullah Al Shafi (Cardiovascular Journal, 2021)
Background: Heart failure is a complex clinical syndrome that arises secondary to abnormalities of cardiac structure and/or function (inherited or acquired) that impair the ability of the left ventricle to fill or eject blood. There is a paucity of data on characteristics of the patients of heart failure admitted in hospitals in terms of demographic and etiological information. So, this study aimed to see the disease burden of heart failure patients and the age and sex specific prevalence of heart failure among patients admitted into NICVD and to identify the etiological pattern of diseases leading to heart failure with associated comorbid factors. Methods: It was a cross sectional study carried out at National Institute of Cardiovascular Diseases (NICVD) Dhaka Bangladesh and was conducted from January 2015 to December 2015. Total 400 heart failure patients were taken. Results: The mean age of the patients were 54 ± 14 years ranging from 16 to 95 years with a high preponderance of male. Most the patient population was in the age group of 51- 60 years (29.5%). 79% of the cases were male & 21% female by gender specification. Ischaemic cardiomyopathy (ICM) was found to be the common cause of heart failure (n=153, 40.75%) followed by Acute coronary syndrome (32.5%) and Valvular heart disease (18.25%). The patients with heart failure having acute coronary syndrome (n=107) had hypertension (46.8%) as the most prevalent major risk factor. In the present study only 11% patient had heart failure with preserved ejection fraction. Mortality rate of the study population were 6.3%. Conclusion: In this study, the most common cause of heart failure is ischaemic heart disease. So, patients of acute and chronic ischemic heart disease patients should be treated and follow up with care. Clinical and epidemiological studies are needed to explore further. Cardiovasc. j. 2021; 13(2): 172-176